PENGARUH MUTASI DAN PROMOSI JABATAN TERHADAP KINERJA PEGAWAI - Farhan Ramdhani Istianandar; Abdul Razak Yusuf; Wa Ode Ungku Sara (Pascasarjana Universitas Halu Oleo, 2023)
This study aims to determine the effect of mutations and promotions on employee performance at the Kendari City BKPSDM Office. The analytical method used is multiple linear regression analysis with the help of SPSS 21. And the measurement tool used is in the form of questionnaires, namely as many as 32 questionnaires.The results of this study indicate that simultaneously mutation and promotion have a positive and significant effect on employee performance with a correlation coefficient value of 0.492 or 49.2% which has a moderate influence category. Partially, mutations have a positive and significant effect on employee performance with a correlation coefficient of 0.537 or 53.7% which has a moderate influence category. Partially promotion has a positive and significant effect on employee performance with a correlation coefficient value of 0.472 or 47.2% which has a moderate influence category